Same-sex couples and adoption : a study of two families. - De Wet, Leigh. (2012)
Increasingly, same-sex couples are choosing to become parents. According to Patterson (1992, cited in Mallon, 1997), it is estimated that in the United States of America alone, there are between six and 14 million children being raised by gay and lesbian couples. This study explored the experiences of same-sex parents as they moved through the adoption process, and once they had become parents. Two couples (a gay male couple and a lesbian couple) were interviewed. The study used an ecological theoretical framework in order to understand the myriad influences on the individuals' and couples' experiences. The Voice-Centred Relational Method (Mauthner & Doucet, cited in Ribbens & Edwards, 1998) was used to analyse the data qualitatively. Major themes that emerged from the data include the ways in which parents negotiate roles with partners, the impact of societal reactions (and heteronormativity) on the couples, the quality of relationships between family members and the influence that these had on the couples' experience of parenting. === Thesis (M.A.)-University of KwaZulu-Natal, 2007.